(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article discusses the role of social networks in modern society and their positive and negative impact on the spiritual and moral education of young people. It also analyzes the importance of proper internet use, the formation of spiritual immunity among youth, and the role of parents and teachers in the educational process